The glorious contribution of Ibn al-Quff on cardiology and embryology as well as other surgical matters - Mohd Nasir, Nur Aimi; Mirghani, Mohamed Elwathig Saeed (IIUM Press, 2011)
This chapter investigates the contribution of Ibn Al- Quff on cardiology and embryology as well as other surgical matters. He was a physician with five major interests which were anatomy, embryology, clinical medicine, surgery and prevention (Athar, 2010). Additionally, Ibn AI-Quff or his full name Amin AI-Dawlah Abu al Faraj Ibn Yaqub ibn Ishaq Ibn al-Quff al-Karaki was born 22nd of August 1233 and death in 1286, in Damascus, Syria. The methodologies adopted in this chapter are library and internet based collections data such as journals and books. The significance of this research are to preserve and develop the innovation works which had been done by Ibn AI-Quff in promotion to the medicine era as well as to encourage the young physicians nowadays to follow Ibn Al Quff in specifically to invent something noble for the goods of the society. The main objective of this chapter is to investigate Ibn Al Quff's contribution as a physician specifically in medicine area of cardiology, embryology and surgery. Besides, to study how Ibn AI-Quff did innovations specifically on these areas. Moreover, his explanation on his research is also explored